Law No. 4 of the Year 2019 Amending Certain Provisions of Law No. 196 of the Year 2008 Promulgating Law on Built Real Estate Tax = قانون رقم 4 لسنة 2019 بتعديل بعض أحكام القانون رقم 196 لسنة 2008 بإصدار قانون الضريبة على العقارات المبنية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic